Current treatment approaches to mixed-etiology vulvovaginitis during pregnancy - E.V. Shaposhnikova (LCC «Medicine-Inform», 2021)
E.V. Shaposhnikova Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation Infections contribute greatly to the unfavorable course of pregnancy and gestational complications. Published data suggest a significant role of mixed infections and coinfections in vulvovaginitis as well as their association with intraamniotic infections caused by multiple microbes. This paper analyzes the studies on the current diagnostic and treatment approaches to mixed-etiology vulvovaginitis during pregnancy depending on gestational age and whether a medication is incorporated into the current clinical guidelines. The use of combination drugs with confirmed efficacy and broad-spectrum antimicrobial, fungicide, and antiprotozoal activity considering risk-benefit ratio for the mother and the child is highlighted. The efficacy of topical combination of metronidazole and miconazole for mixed-etiology vulvovaginitis during pre-pregnancy preparation and pregnancy based on various dosing regimens and the duration of use is addressed. Keywords: pregnancy, vulvovagini tis, bacterial vaginosis, topical treatment, metronidazole, miconazole. For citation: Shaposhnikova E.V. Current treatment approaches to mixed-etiology vulvovaginitis during pregnancy. Russian Journal of Woman and Child Health. 2021;4(1):5-11. DOI: 10.32364/2618-8430-2021-4-1-5-11.